Характер успадкування ознак T. spelta L. чорнобильськими мутантами пшениці м’якої озимої - Бурденюк-Тарасевич, Л.А. (Фактори експериментальної еволюції організмів, 2013)
Aims. The study was conducted to determine the morphological and biological characteristics of different forms of spelled, formed as a result of irradiation of four varieties of winter wheat-T. aestivum–Myronivska 808, Belotserkovskaya 47, Woodland 70 and Kiyanka, in the exclusion zone of the Chernobyl Nuclear Power Station. It was necessary to ascertain the nature of inheritance trait speltoyidnosti and specificity of mutational changes depending on the genotype of the variety. Methods. Every year, during the 25 generations (1988–2012) the forms that differed from the original varieties were selected by ear and by re-seeded by pedigree method. Morphological analysis of ears was conducted (20 ears each class of mutants). The length of spike, number of spikelets in the ear, flowers and grains in the ears of the upper and lower half of the ear, the percentage of sterile flowers and code density (ears 10 cm rod spike), the number of grains in the ear and their weight were determined. To determine the mutation inheritance character reciprocal and analyzing crosses of T. spelta mutants with original varieties were conducted. Results. The wide variety of winter wheat mutations was discovered as a result of radiological irradiation. The spectrum of mutations was widening from generation to generation due to unstable mutagenesis. Analyzing crossing has proven the recessive character of the mutations noted. Mutation process is dependent on variety genotype. Conclusions. Mutations prove the important role of mutagenesis in evolution of T. aestivum wheat.

Key words: Chernobyl mutants, crossings, winter wheat, T. aestivuт, T. spelta.